2017
DOI: 10.1038/s41598-017-01769-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved thrombolytic effect with focused ultrasound and neuroprotective agent against acute carotid artery thrombosis in rat

Abstract: Combination therapy with focused ultrasound (FUS) and a neuroprotective agent, BNG-1, was examined in an acute carotid thrombotic occlusion model using LED irradiation in rat to improve the thrombolytic effect of rt-PA. Seven treatment groups included (A) intravenous bolus injection of 0.45 mg/kg rt-PA, (B) intravenous bolus injection of 0.9 mg/kg, (C) sonothrombolysis with FUS alone, (D) oral administration of 2 g/kg BNG-1 for 7 days alone, (E) A + D, (F) A + C, and (G) A + C + D. Four comparison groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…The low acute recanalization rate with intravenous recombinant tPA highlights the need for further studies regarding the acceleration of intravenous thrombolysis [25]. Multiple in vitro and animal studies have demonstrated the efficacy of ultrasound in accelerating therapeutic fibrinolysis [26][27][28]. In the present meta-analysis, we assessed the data collected in five RCTs evaluating the clinical safety and efficacy of sonothrombolysis in patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The low acute recanalization rate with intravenous recombinant tPA highlights the need for further studies regarding the acceleration of intravenous thrombolysis [25]. Multiple in vitro and animal studies have demonstrated the efficacy of ultrasound in accelerating therapeutic fibrinolysis [26][27][28]. In the present meta-analysis, we assessed the data collected in five RCTs evaluating the clinical safety and efficacy of sonothrombolysis in patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that combining diagnostic ultrasound with microbubbles can accelerate the fibrinolysis induced by urokinase (54 kDa) [ 115 ] and recombinant tissue plasminogen activator (rtPA, 70 kDa) [ 116 ], supporting that acoustic cavitation is one mechanism for accelerating thrombolysis. Similarly, Lee et al showed in an in vivo model that low-dose rtPA combined with FUS can produce thrombolysis equivalent to that for full-dose rtPA without FUS [ 117 ]. Wang et al further developed a clot-targeted microbubble that induced a superior clot-lysis effect compared with the untargeted group using 800 kHz therapeutic ultrasound [ 118 ].…”
Section: Other Cns Applicationsmentioning
confidence: 99%
“…They also suggested that with the reduction in acoustic power and the use of transducers with precision focus, HIFU thrombolysis can be achieved successfully within the main arteries of human brain without causing any vascular damage and bleeding of the sonicated vessels. A recent preclinical study examined combination therapy of HIFU and a neuroprotective agent BNG‐1 in an acute carotid thrombotic occlusion model using light‐emitting diode (LED) irradiation in rat to improve the thrombolytic effect of rt‐PA …”
Section: In‐vivo Hifu Studiesmentioning
confidence: 99%
“…They also suggested that with the reduction in acoustic power and the use of transducers with precision focus, HIFU thrombolysis can be achieved successfully within the main arteries of human brain without causing any vascular damage and bleeding of the sonicated vessels. A recent preclinical study examined combination therapy of HIFU and a neuroprotective agent BNG-1 in an acute carotid thrombotic occlusion model using light-emitting diode (LED) irradiation in rat to improve the thrombolytic effect of rt-PA. 68 As apparent from numerous preclinical studies, HIFU sonothrombolysis has lately emerged as a favorable tPA-free option for the treatment of AIS. [60][61][62][63][64][65] HIFU causes microbubble oscillation which causes mechanical disruption of the blood clot improving flow restoration.…”
Section: In-vivo Hifu Studiesmentioning
confidence: 99%